MyScope : a National Approach to Education in Advanced Microscopic Characterisation Through Integrated Learning Tools : Final Report. - Cribb, Bronwen; White, Tim; Munroe, Paul; Shapter, Joe; Muhling, Janet; Frost, Chris; Whittington, Matthew (Office for Learning and Teaching, 2013)
Final report from a project that aimed to lead a broad transformation of educational resources. In microscopy based characterisation, national surveys and meetings have established that there are two deficiencies: 1) traditional pedagogies do not optimally serve a growing student body needing this education in Australia, and 2) the diversity of this cohort cannot be adequately addressed within the current educational model. These challenges can be met with a new approach - the development and integration of a flexible and comprehensive blended learning program to create an enhanced education landscape available at a national level. This project brings together a team of experts in research-led teaching from six universities and will harness, extend and harmonise innovations in teaching and learning developed by them individually. The project is large in scope and is designed to complement a major education and e-research focus provided by the Australian Microscopy & Microanalysis Research Facility.